Validation of a Novel Fluorescent Lateral Flow Assay for Rapid Qualitative and Quantitative Assessment of Total Anti-SARS-CoV-2 S-RBD Binding Antibody Units (BAU) from Plasma or Fingerstick Whole-Blood of COVID-19 Vaccinees - Younes, Nadin (2022)
Background: Limited commercial LFA assays are available to provide a reliable quantitative measurement of the total binding antibody units (BAU/mL) against the receptor-binding domain of the SARS-CoV-2 spike protein (S-RBD). Aim: This study aimed to evaluate the performance of the fluorescence LFA FinecareTM 2019-nCoV S-RBD test along with its reader (Model No.: FS-113) against the following reference methods: (i) the FDA-approved GenScript surrogate virus-neutralizing assay (sVNT); and (ii) three highly performing automated immunoassays: BioMérieux VIDAS®3, Ortho VITROS®, and Mindray CL-900i®. Methods: Plasma from 488 vaccinees was tested by all aforementioned assays. Fingerstick whole-blood samples from 156 vaccinees were also tested by FinecareTM. Results and conclusions: FinecareTM showed 100% specificity, as none of the pre-pandemic samples tested positive. Equivalent FinecareTM results were observed among the samples taken from fingerstick or plasma (Pearson correlation r = 0.9, p < 0.0001), suggesting that fingerstick samples are sufficient to quantitate the S-RBD BAU/mL. A moderate correlation was observed between FinecareTM and sVNT (r = 0.5, p < 0.0001), indicating that FinecareTM can be used for rapid prediction of the neutralizing antibody (nAb) post-vaccination. FinecareTM BAU results showed strong correlation with VIDAS®3 (r = 0.6, p < 0.0001) and moderate correlation with VITROS® (r = 0.5, p < 0.0001) and CL-900i® (r = 0.4, p < 0.0001), suggesting that FinecareTM can be used as a surrogate for the advanced automated assays to measure S-RBD BAU/mL.